A study on the intention to purchase Halal cosmetics product among Generation-Y / Nurlyiana Mohd Ali - Mohd Ali, Nurlyiana (Faculty of Business and Management, 2016)
The purpose of the study is to determine the level of intention to purchase Halal cosmetics product among Generation-Y. This study also identifies the antecedent factors that influence the intention to purchase Halal cosmetics product among Generation-Y. Knowledge and perceived quality have been found to influence Generation-Y to purchase Halal cosmetics product. The findings indicate that there is a relationship between independent variables (knowledge and perceived quality) and dependent variable. Meanwhile, this study found that there is no relationship between religiosity and dependent variable.